CULTURE SHOCK, SELF-PRESERVATION IN INTERNATIONAL CULTURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article analyzes the wonder of culture stun (social weakness), confronted by nearly each individual within the interaction with the unused culture. The creator presents the characteristics of the most shapes of social stun, its causes and indications. The article portrays the improvement stages of culture stun: special night, «grinding», «reintegration», «neutrality», «comfort», conjointly U-shaped and W-shaped show adaptation. The article analyzes the internal (personal) factors that affect the strength of the symptoms of culture shock and the duration of intercultural adaptation: age, gender, education, personality traits of the person, life experience, motivation, and external (group) factors: cultural distance, the features of the native culture of the migrant and other. The author discusses ways of conduct in order to prevent or reduce the duration of culture shock: ghettoizing, assimilation, interaction, partial assimilation. In conclusion, in this problem, the author summarizes the results concerning the current areas of research of culture shock.